Integrating Knowledge of Vertically Aligned Large-Scale Spaces - Montello, Daniel R.; Pick, Herbert L. (Environment and behavior, 1993)
The acquisition and integration of configurational knowledge of spatial layout was studied in a large building complex containing several levels. Twenty-four college students learned two separate routes by walking around the complex; the two were located one above the other, although this was not visibly apparent. Subjects were then given a description that allowed them to integrate their knowledge of the two routes. Straight-line pointing errors and latencies revealed that subjects acquired considerable configurational knowledge about each route and about their relationship, although pointing was slower and less accurate between than within routes. The study demonstrates integration of separately learned spaces in a naturalistic setting, important to theories of environmental learning. It also provides data on learning in vertically aligned spaces and further evidence of the utility of self-report sense of direction as an individual-difference measure.